Electrical Restitution and Its Modifications by Antiarrhythmic Drugs in Undiseased Human Ventricular Muscle - Árpádffy-Lovas, Tamás; Baczkó, István; Baláti, Beáta; Bitay, Miklós; Jost, Norbert; Lengyel, Csaba; Nagy, Norbert; Takács, János; Varró, András; Virág, László (Frontiers in Pharmacology, 2020)
INTRODUCTION Re entry is a basic mechanism of ventricular fibrillation, which can be elicited by extrasystolic activity, but the timing of an extrasystole can be critical. The action potential duration (APD) of an extrasystole depends on the proximity of the preceding beat, and the relation between its timing and its APD is called electrical restitution. The aim of the present work was to study and compare the effect of several antiarrhythmic drugs on restitution in preparations from undiseased human ventricular muscle, and other mammalian species. METHODS Action potentials were recorded in preparations obtained from rat, guinea pig, rabbit and dog hearts; and from undiseased human donor hearts using conventional microelectrode techniques. Preparations were stimulated with different basic cycle lengths (BCLs) ranging from 300 to 5000 ms. To study restitution, single test pulses were applied at every 20th beat while the preparation was driven at 1000 ms BCL. RESULTS Marked differences were found between the animal and human preparations regarding restitution and steady-state frequency dependent curves. In human ventricular muscle, restitution kinetics were slower in preparations with large phase 1 repolarization with shorter APDs at 1000 ms BCL compared to preparations with small phase 1. Preparations having APD longer than 300 ms at 1000 ms BCL had slower restitution kinetics than those having APD shorter than 250 ms. The selective IKr inhibitors E 4031 and sotalol increased overall APD and slowed the restitution kinetics, while IKs inhibition did not influence APD and electrical restitution. Mexiletine and nisoldipine shortened APD, but only mexiletine slowed restitution kinetics. DISCUSSION Frequency dependent APD changes, including electrical restitution, were partly determined by the APD at the BCL. Small phase 1 associated with slower restitution suggests a role of Ito in restitution. APD prolonging drugs slowed restitution, while mexiletine, a known inhibitor of INa, shortened basic APD but also slowed restitution. These results indicate that although basic APD has an important role in restitution, other transmembrane currents, such as INa or Ito, can also affect restitution kinetics. This raises the possibility that ion channel modifier drugs slowing restitution kinetics may have antiarrhythmic properties by altering restitution.